Renin-angiotensin system blockade on angiotensin-converting enzyme 2 and TMPRSS2 in human type II pneumocytes - Silva, Mauro G.; Falcoff, Nora L.; Corradi, Gerardo R.; Alfie, José; Seguel, Rolando F.; Tabaj, Gabriela C.; Iglesias, Laura I.; Nuñez, Myriam; Guman, Gabriela R.; Gironacci, Mariela M. (Life sciences (1973), 2022)
Angiotensin-converting enzyme (ACE) 2 is the receptor for severe acute respiratory syndrome coronavirus 2 which causes coronavirus disease 2019 (COVID-19). Viral cellular entry requires ACE2 and transmembrane protease serine 2 (TMPRSS2). ACE inhibitors (ACEIs) or angiotensin (Ang) receptor blockers (ARBs) influence ACE2 in animals, though evidence in human lungs is lacking. We investigated ACE2 and TMPRSS2 in type II pneumocytes, the key cells that maintain lung homeostasis, in lung parenchymal of ACEI/ARB-treated subjects compared to untreated control subjects. Ang II and Ang-(1–7) levels and ACE2 and TMPRSS2 protein expression were measured by radioimmunoassay and immunohistochemistry, respectively. We found that the ratio Ang-(1–7)/Ang II, a surrogate marker of ACE2 activity, as well as the amount of ACE2-expressing type II pneumocytes were not different between ACEI/ARB-treated and untreated subjects. ACE2 protein content correlated positively with smoking habit and age. The percentage of TMPRSS2-expressing type II pneumocytes was higher in males than females and in subjects under 60 years of age but it was not different between ACEI/ARB-treated and untreated subjects. However, there was a positive association of TMPRSS2 protein content with age and smoking in ACEI/ARB-treated subjects, with high TMPRSS2 protein levels most evident in ACEI/ARB-treated older adults and smokers. ACEI/ARB treatment influences human lung TMPRSS2 but not ACE2 protein content and this effect is dependent on age and smoking habit. This finding may help explain the increased susceptibility to COVID-19 seen in smokers and older patients with treated cardiovascular-related pathologies.